Three new species of the Andean genus Brunellia (Brunelliaceae) from Colombia and Ecuador - Orozco, Clara Inés; Pérez, Álvaro J.; Romoleroux, Katya; Bohórquez-Osorio, Andrés Felipe; Aldana, José Murillo (Phytotaxa, 2020)
Three new species of Brunellia are described; their morphology and affinities with other species and their conservation status are discussed. Two of them are endemic to Colombia: Brunellia alnifolia, characterized by three simple and verticellate leaves per node and boat–shaped endocarps, and Brunellia gracilis, with pinnate leaves and urceolate endocarps. The third species, Brunellia hippocrepiformis, is endemic to Ecuador. On account of the morphology of leaves, stipules and follicles, it differs from all other Brunellia species.